Na-Influenced Bulk and Surface Properties of the So-Called Iota(ι)-Alumina: Spectroscopy and Microscopy Studies - Bumajdad, Ali; Nahar, Shamsun; Zaki, Mohamed I. (Frontiers in Chemistry, 2021)
The test alumina (the so-called ι-Al2O3) was thermally recovered at 1,100°C from chitosan-AlOx hybrid films and found to contain Na and Ca impurity ions inherited from the parent chitosan. Two different modifications of pure alumina, namely, γ- and α-Al2O3, were adopted as control samples. The test and control aluminas were examined for 1) the bulk elemental constitution by atomic absorption spectroscopy (AAS), 2) the surface chemical composition by X-ray photoelectron spectroscopy (XPS), 3) the bulk phase composition by X-ray powder diffractometry (XRD), ex-situ Fourier-transform infrared spectroscopy (IR), and Laser Raman (LRa) spectroscopy, 4) the surface area, topography, and morphology by N2 sorptiometry, and atomic force (AFM) and scanning electron microscopy (SEM), 5) the surface adsorptive interactions with pyridine and 2-propanol gas-phase molecules by in-situ IR spectroscopy of the adsorbed species, and 6) the surface catalytic interactions with 2-propanol gas-phase molecules by in-situ IR spectroscopy of the gas phase. Results obtained could clearly show that the test alumina (ι-Al2O3) is only hypothetically pure alumina since in reality its bulk structure is majored by mullite-type Na-aluminate (Na0.67Al6O9.33/NaAlO2) and minored by Na-β-alumina (Na1.71Al11O17) and β-alumina (NaAl11O17). Consistently, observed Na-influenced modifications of the surface chemistry, topology, and morphology, as well as adsorptive and catalytic interactions with pyridine and 2-propanol gas-phase molecules, showed significant deviations from those exhibited by the control pure aluminas (γ- and α-Al2O3).